GPS-Based AR Games Development Potential - Santoso, Gregorius Alvin Raditya (Soegijapranata Catholic University, 2014)
The application of new technologies in a game is not a new thing. One example is the application of Augmented Reality (AR) technology in game. Many people do not know the application of AR technology in game, although the application of this technology is able to produce a game with unique gameplay. In addition, since AR game is GPS-based, it offers new gaming experience, that is, playing outdoors in which the real world becomes the game arena. This advantage gives the AR technology a huge potential to be developed into a game